Comparison of Antibody Responses and Parasite Clearance in Artemisinin Therapeutic Efficacy Studies in the Democratic Republic of Congo and Asia. (15th June 2022) - Cutts, Julia C; O'Flaherty, Katherine; Zaloumis, Sophie G; Ashley, Elizabeth A; Chan, Jo Anne; Onyamboko, Marie A; Fanello, Caterina; Dondorp, Arjen M; Day, Nicholas P; Phyo, Aung Pyae; Dhorda, Mehul; Imwong, Mallika; et al.
Abstract: Background: Understanding the effect of immunity on Plasmodium falciparum clearance is essential for interpreting therapeutic efficacy studies designed to monitor emergence of artemisinin drug resistance. In low-transmission areas of Southeast Asia, where resistance has emerged, P. falciparum antibodies confound parasite clearance measures. However, variation in naturally acquired antibodies across Asian and sub-Saharan African epidemiological contexts and their impact on parasite clearance re yet to be quantified. Methods: In an artemisinin therapeutic efficacy study, antibodies to 12 pre-erythrocytic and erythrocytic P. falciparum antigens were measured in 118 children with uncomplicated P. falciparum malaria in the Democratic Republic of Congo (DRC) and compared with responses in patients from Asian sites, described elsewhere. Results: Parasite clearance half-life was shorter in DRC patients (median, 2 hours) compared with most Asian sites (median, 2–7 hours), but P. falciparum antibody levels and seroprevalences were similar. There was no evidence for an association between antibody seropositivity and parasite clearance half-life (mean difference between seronegative and seropositive, −0.14 to +0.40 hour) in DRC patients. Conclusions: In DRC, where artemisinin remains highly effective, the substantially shorter parasite clearance time compared with Asia was not explained by differences in the P. falciparum antibody responses studied. Abstract : The substantially shorter Plasmodium falciparum parasite clearance time after artemisinin treatment observed in an African site, where artemisinin remains highly effective, compared with Asian sites, cannot be explained by differences in naturally acquired P. falciparum antibody responses.